Heterocyclic Compounds from Marine Organisms - Barbero, Asunción (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Marine drugs have drawn considerable attention due to their significant biological and pharmacological properties, such as antimicrobial or antibacterial activities and antitumor effects, among others. The frequent occurrence of heterocyclic motifs in the structure of many of these targets has revealed the key role of these units as promising pharmacophores. In this Special Issue we have gathered several original papers which highlight the isolation, structural elucidation and biological essays of newly isolated heterocyclic marine drugs, as well as reviews which give an overview of the isolation, synthesis and pharmacological activities of different classes of marine heterocycles.